The potent antimicrobial properties of cell penetrating peptide-conjugated silver nanoparticles with excellent selectivity for Gram-positive bacteria over erythrocytes - Liu, Lihong; Yang, J.; Xie, J.; Luo, Z.; Jiang, J.; Yang, Y.Y.; Liu, Shaomin (R S C Publications, 2013)
Silver nanoparticles are of great interest for use as antimicrobial agents. Studies aimed at producing potentnano-silver biocides have focused on manipulation of particle size, shape, composition and surface charge.Here, we report the cell penetrating peptide catalyzed formation of antimicrobial silver nanoparticles inN,N-dimethylformamide. The novel nano-composite demonstrated a distinctly enhanced biocidal effecttoward bacteria (Gram-positive Bacillus subtilis, Gram-negative Escherichia coli) and pathogenic yeast(Candida albicans), as compared to triangular and extremely small silver nanoparticles. In addition, asatisfactory biocompatibility was verified by a haemolysis test. Our results provide a paradigm indeveloping strategies that can maximize the silver nanoparticle application potentials while minimizingthe toxic effects.